Novel Trauma Composite Score is superior to Injury Severity Score in predicting mortality across all ages. Issue 4 (6th October 2021) - Keskey, Robert C.; Slidell, Mark B.; Bohr, Nicole L.; Biermann, Henry; Cirone, Justin; Zakrison, Tanya; Cone, Jennifer; Wilson, Kenneth; Hampton, David
Abstract : Supplemental digital content is available in the text. Abstract : BACKGROUND: Injury Severity Score (ISS) is a widely used metric for trauma research and center verification; however, it does not account for age-related physiologic parameters. We hypothesized that a novel age-based injury severity metric would better predict mortality. METHODS: Adult patients (≥18 years) sustaining blunt trauma (BT) or penetrating trauma (PT) were abstracted from the 2010 to 2016 National Trauma Data Bank. Admission vitals, Glasgow Coma Scale, ISS, mechanism, and outcomes were analyzed. Patients with incomplete/non-physiologic vital signs were excluded. For each age: (1) a cut point analysis was used to determine the ISS with the highest specificity and sensitivity for predicting mortality and (2) a linear discriminant analysis was performed using ISS, ISS greater than 16, Trauma and Injury Severity Score, and Revised Trauma Scale to compare each scoring system's mortality prediction. A novel injury severity metric, the trauma component score (TCS), was developed for each age using significant ( p < 0.05) variables selected from Abbreviated Injury Scale scores, Glasgow Coma Scale, vital signs, and gender. Receiver operator curves were developed and the areas under the curve were compared between the TCS and other systems. RESULTS: There 777, 794 patients studied (BT, 91.1%; PT, 8.9%). Blunt trauma patients were older (53.6 ± 21.3 years vs. 34.4 ± 13.8 years), had higher ISS scores (11.1 ± 8.5 vs. 8.5 ± 8.9), and lower mortality (2.9% vs. 3.4%) than PT patients ( p < 0.05). When assessing the entire PT and BT cohort the optimal ISS cut point was 16. The optimal ISS was between 20 and 25 for BT younger than 70 years. For those older than 70 years, the optimal BT ISS steadily declined as age increased PT's cut point was 16 or less for all ages assessed. When the injury metrics were compared by area under the curve, our novel TCS more accurately predicted mortality across all ages in both BT and PT ( p < 0.001). CONCLUSION: Injury Severity Score is a poor mortality predictor in older patients and those sustaining penetrating trauma. The age-based TCS is a superior metric for mortality prediction across all ages. LEVEL OF EVIDENCE: Clinical outcomes, Level IV.